2020
DOI: 10.1161/circimaging.119.009536
|View full text |Cite
|
Sign up to set email alerts
|

Sonothrombolysis Improves Myocardial Dynamics and Microvascular Obstruction Preventing Left Ventricular Remodeling in Patients With ST Elevation Myocardial Infarction

Abstract: Background: It has recently been demonstrated that high-energy diagnostic transthoracic ultrasound and intravenous microbubbles dissolve thrombi (sonothrombolysis) and increase angiographic recanalization rates in patients with ST-segment–elevation myocardial infarction. We aimed to study the effect of sonothrombolysis on the myocardial dynamics and infarct size obtained by real-time myocardial perfusion echocardiography and their value in preventing left ventricular remodeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
7
1
2
Order By: Relevance
“…Patients in sonothrombolysis group had a higher recanalization rate and TIMI flow before PCI, and reduced infarct size on CMR, resulting in sustained improvements in LVEF and less need for intracardiac defibrillator placement at 6 months follow-up. Furthermore, a substudy showed improved LV global longitudinal strain and decreased perfusion defect size by MCE at follow up, and the only independent predictor of LV remodeling was treatment with sonothrombolysis ( 106 ). As contrast ultrasound is portable, this technique was also shown to have a promising feasibility of in-ambulance sonothrombolysis for STEMI ( 107 ).…”
Section: Applications Of Mce In the Treatment Of Cmdmentioning
confidence: 99%
“…Patients in sonothrombolysis group had a higher recanalization rate and TIMI flow before PCI, and reduced infarct size on CMR, resulting in sustained improvements in LVEF and less need for intracardiac defibrillator placement at 6 months follow-up. Furthermore, a substudy showed improved LV global longitudinal strain and decreased perfusion defect size by MCE at follow up, and the only independent predictor of LV remodeling was treatment with sonothrombolysis ( 106 ). As contrast ultrasound is portable, this technique was also shown to have a promising feasibility of in-ambulance sonothrombolysis for STEMI ( 107 ).…”
Section: Applications Of Mce In the Treatment Of Cmdmentioning
confidence: 99%
“…Ultrasound-guided thrombolysis is one of the most specific targeted tactics to improve thrombus dissolution. Previous studies have shown that the addition of sonothrombolysis before and after emergency PCI for acute STEMI can immediately improve microvascular flow (22,23). Microbubble cavitation induced by US has both catalytic and flow-inducing properties, and this approach takes advantage of these properties to create flow.…”
Section: Enhancing the Microcirculation By Using Better Techniquesmentioning
confidence: 99%
“…A clinical study conducted by Chen et al showed the effectiveness of LIPUS as a combined therapy with alteplase in intravenous thrombosis for vascular recanalization in acute ischemic stroke [ 125 ]. Additionally, Aguiar et al demonstrated the efficacy of LIPUS in reducing microvascular obstruction and improving myocardial dynamics in patients with ST-segment elevation [ 126 ].…”
Section: Applications Of Low-intensity Continuous Ultrasoundmentioning
confidence: 99%